Is uncertain vulvovaginal candidiasis a marker of vulvodynia? A study in a Dutch general practice research database - Leusink, Peter (BJGP Open, 2017)
BACKGROUND: A recent Dutch study in general practice showed a clear relationship between the diagnosis of vulvovaginal candidiasis (VVC) and symptoms suggestive of provoked vulvodynia (PVD). PVD accounts for the largest group of vulvar pains, but is often not recognised by GPs. AIM: To investigate whether diagnostic uncertainty about VVC in general practice could also point to the diagnosis of PVD, and whether and how this diagnostic uncertainty affects management. DESIGN & SETTING: An observational study in 2014 in Dutch general practices of the NIVEL Primary Care Database. METHOD: Women with an uncertain diagnosis of VVC were distinguished from those with certain VVC based on the occurrence of recurrent episodes and persisting complaints, despite treatment. Factors known to be associated with PVD were hypothesised to be more prevalent in women with uncertain VVC. Data on symptom management by GPs were collected. RESULTS: In total 7066 women with VVC or uncertain VVC were included. Uncertain VVC was found to account for 28% of these patients. Compared to VVC, the group uncertain VVC included significantly more women with female genital symptoms, tiredness, irritable bowel syndrome (all P<0.001), feeling anxious, reduced sexual desire, depressive disorder, relationship problems, and micturition symptoms (all P<0.05). Compared to VVC, the group uncertain VVC included significantly higher mean numbers of telephone consultations (P<0.001), more referrals to gynaecology (P = 0.009), and higher mean numbers of prescriptions per patient (P<0.001). CONCLUSION: This study's findings indicate that uncertain VVC could be a marker of PVD. GPs might reconsider their diagnostics and management when women present recurrent and persistent vulvovaginal complaints, especially if accompanied by dyspareunia, functional syndromes, micturition symptoms, and psychological conditions.